Study on drug profile used in diabetic foot ulcer - Ramesh, Rajalakshmi; Moorthi, Kowsalya; Kunchithapatham, Saravanan; Mariappan, Prema (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objective was to study about the drugs used in management of diabetic foot ulcer (DFU) and to grade the wounds using Wagner’s scale. Methods: An observational study was conducted at Department of Pharmacy, Rajah Muthiah Medical College Hospital over a period of six months from November 2018 to April 2019. The data was collected from 85 patients using data collection form. The patients were selected based on inclusion and exclusion criteria. Results: Overall 85 patients were enrolled in this study. The prevalence of DFU found to be 36% more in males 58 (68%) than in females 27 (32%). Considering the age group, higher prevalence was reported in patients among the age group of 60-70. This study shows, patients were found commonly to have habits of alcohol 18 (21%), smoking 11 (13%) and both 22 (26%). Overall, 23 classes of drugs were used in this study. Among these, mostly were antibiotics 12 (52%) then hypoglycemic drugs 5 (21%) and others are analgesics (9%), anti-ulcerant and vitamins. This study shows that the common antibiotics prescribed are metronidazole 39 (24%), cefotaxime 36 (22.7%), ciprofloxacin 25 (15.8%) and piperacillin 21 (13.2%). The common hypoglycemic drug used were of insulin 63 (74%), metformin 43 (77%), glimepiride 12 (14%) and metformin and glimepiride 12 (14%). By using Wagner’s scale, out of 85 patients, most of the ulcer were predominantly between grade IV and V. Conclusions: Targeting range of glycaemic levels and proper antibiotics is the best way of treating DFU. This study has provided the base line data regarding management of DFU which helps to improve therapeutic outcome.